Complex dynamics of a three species food-chain model with Holling type IV functional response - Upadhyay, Ranjit Kumar Kumar; Raw, Sharada Nandan Nandan (Nonlinear Analysis: Modelling and Control, 2011)
In this paper, dynamical complexities of a three species food chain model with Holling type IV predator response is investigated analytically as well as numerically. The local and global stability analysis is carried out. The persistence criterion of the food chain model is obtained. Numerical bifurcation analysis reveals the chaotic behavior in a narrow region of the bifurcation parameter space for biologically realistic parameter values of the model system. Transition to chaotic behavior is established via period-doubling bifurcation and some sequences of distinctive period-halving bifurcation leading to limit cycles are observed.